2010
DOI: 10.1007/s11250-009-9524-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on egg, meat, and semen qualities of native and improved chicken varieties developed for backyard poultry production

Abstract: The objective of the present study was to evaluate/compare the sensory attributes of eggs and meat, egg qualities, proximate composition of eggs, and semen qualities of slow growing native (Miri and Mizo-local) and fast growing improved chicken varieties (Gramapriya and Vanaraja) under hill ecosystem of northeastern India. Significantly higher egg weight, egg volume, and albumen volume were observed in Gramapriya followed by Vanaraja, Mizo-local, and Miri chickens. However, yolk volume was significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…However, the earliest slaughtering time in our experiment (12 weeks) led to average values of 23.16N and 23.64N for Ho, and Dong Tao, respectively, which is definitely much higher than these commercial standards. Genetic differences between breeds and the slaughter age can affect the tenderness of chicken meat [27,28]. Our study supports these hypotheses, showing differences between breeds, and a decrease of the tenderness with the age at slaughter.…”
Section: Egg Productionsupporting
confidence: 86%
“…However, the earliest slaughtering time in our experiment (12 weeks) led to average values of 23.16N and 23.64N for Ho, and Dong Tao, respectively, which is definitely much higher than these commercial standards. Genetic differences between breeds and the slaughter age can affect the tenderness of chicken meat [27,28]. Our study supports these hypotheses, showing differences between breeds, and a decrease of the tenderness with the age at slaughter.…”
Section: Egg Productionsupporting
confidence: 86%
“…This is also in conformity with reports of Haunshi et al . [ 25 ]. Similar to present finding, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a higher BW, the Aseel breed showed no significant difference from the Kadaknath breed in the volume of ejaculate; however, a slightly higher average volume of ejaculate was observed in the Kadaknath breed. This finding was somewhat unexpected because it has been established that cockerels with a higher BW will have a greater volume of ejaculate compared with their counterparts with a lower BW (Haunshi et al, 2010). However, Biswas et al (2009) reported a lower volume of ejaculate for the Kadaknath breed at about 30 wk of age.…”
Section: Semen Quality Traitsmentioning
confidence: 92%